Influence of load-bearing angle, structural topology, and porosity gradient on the energy absorption capability of TPMS-based scaffolds for bone tissue engineering - Zhang, Chunli; Lyu, Yongtao; Semenova, Anna; Li, Zhonghai (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTriply periodic minimal surfaces (TPMS) based scaffolds are widely used in bone tissue engineering for fixing bone fractures. The bone scaffolds implanted in the human body may receive shocking or impact loading during daily activities. However their energy absorption (EA) behaviors are still not systematically investigated in the literature.MethodsIn the present study, the influence of load_bearing angle, the structural topology and porosity gradient on the EA behaviors of TPMS-based scaffolds are investigated. Uniform and porosity gradient Gyroid and IWP structures at the load-bearing angles of 0°, 15°, 30°, 45°, 60°, 75° and 90° were created. Mechanical testing and finite element analysis were performed to investigate their EA behaviors, which were characterized using the energy absorption efficiency (EAE), the specific energy absorption (SEA), the levels of the densification strain, plateau stress and stress distribution.ResultsThe results showed that the load-bearing angle plays an important role in EAE, SEA and plateau stress of porosity gradient Gyroid and IWP scaffolds. Different from the uniform TPMS scaffolds, the porosity gradient Gyroid and IWP scaffolds showed layer-to-layer damage behaviors, which reinforced their load-bearing capability and consequently the SEA performance is improved.ConclusionThe data in the present study provided important guidance on the selection and design of TPMS structures for bone tissue engineering applications.